The Implications Of The Covid-19 Pandemic On Oil Prices In The Middle East - Bellabaci ,Zakaria; Hussain ,Ali; Ababba, Ali (جامعة الوادي University of Eloued, 2025)
This This study aims to analyze the implications of the COVID-19 pandemic on oil prices in the Middle East and North Africa (MENA) region, with a focus on the dual shock experienced by the region’s economies as a result of the pandemic outbreak on one hand, and the sharp collapse in global oil prices on the other. The study adopts an economic analytical approach based on both quantitative and qualitative data derived from international reports, with the objective of assessing the crisis's impact on national budgets, expenditure levels, and short- and medium-term economic growth prospects. The findings indicate that an effective response to this dual shock requires prioritizing actions over time—starting with addressing urgent health emergencies, followed by tackling the economic recession, while fiscal consolidation policies may be postponed until the recovery phase begins. The study also emphasizes the need to boost health spending, provide direct cash transfers to vulnerable groups, and support the private sector, especially small and mediumsized enterprises operating in the informal economy, as they represent a critical component in the recovery path and economic restructuring after the crisis.
The Implications of the COVID-19 Pandemic on Oil Prices in the Middle East and North Africa Region: An Analytical Economic Study
مقال
Keywords: COVID-19 pandemic; oil prices; dual shock; economic crisis; OPEC+; MENA countries.